Case Report: A review of two children with deep sternal wound infections after precordial surgery treated with a simple negative pressure closed drainage technique - Jiang, Yao; He, Shan (Frontiers in Pediatrics, 2024)
Deep sternal wound infection (DSWI) is a rare but potentially devasting complication of median sterotomy performed in cardiac surgery.This report summarizes the nursing management of two pediatric cases with DSWI treated using DIY negative pressure suction(DIY-NPS) after surgery. The technique maintains a continuous suction pressure of 75 mmHg and intermittently flushes small volumes of fluid to stimulate granulation tissue formation and control systemic infection. After the formation of fresh granulation tissue, both patients achieved successful wound healing and were discharged in good condition.